1999
DOI: 10.1063/1.873443
|View full text |Cite
|
Sign up to set email alerts
|

Initial physics achievements of large helical device experiments

Abstract: have started this year after a successful eight-year construction and test period of the fully superconducting facility. LHD investigates a variety of physics issues on large scale heliotron plasmas ͑Rϭ3.9 m, aϭ0.6 m͒, which stimulates efforts to explore currentless and disruption-free steady plasmas under an optimized configuration. A magnetic field mapping has demonstrated the nested and healthy structure of magnetic surfaces, which indicates the successful completion of the physical design and the effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
57
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 175 publications
(57 citation statements)
references
References 13 publications
0
57
0
Order By: Relevance
“…This is partly due to the lack of appropriate diagnostics, and partly due to the smallness of the hitherto used stellarators. With the start of the large helical device (LHD) experiment with sophisticated diagnostics [10], we could first (we think) observe the island behavior in a stellarator in the presence of plasma.LHD [11,12] is a superconducting magnet system composed of an L 2͞M 10 helical coil and three pairs of poloidal coils. The currents in these coils are fed independently, allowing us to change the shape and position of the magnetic surfaces as well as the magnetic field strength on axis B ax up to 3 T. The plasmas we analyze in this Letter were produced in two magnetic configurations with different magnetic axis positions: R ax 3.75 and 3.6 m. The poloidal cross sectional views of magnetic field lines at a horizontally elongated section are shown for the R ax 3.6 and 3.75 m configurations in Figs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This is partly due to the lack of appropriate diagnostics, and partly due to the smallness of the hitherto used stellarators. With the start of the large helical device (LHD) experiment with sophisticated diagnostics [10], we could first (we think) observe the island behavior in a stellarator in the presence of plasma.LHD [11,12] is a superconducting magnet system composed of an L 2͞M 10 helical coil and three pairs of poloidal coils. The currents in these coils are fed independently, allowing us to change the shape and position of the magnetic surfaces as well as the magnetic field strength on axis B ax up to 3 T. The plasmas we analyze in this Letter were produced in two magnetic configurations with different magnetic axis positions: R ax 3.75 and 3.6 m. The poloidal cross sectional views of magnetic field lines at a horizontally elongated section are shown for the R ax 3.6 and 3.75 m configurations in Figs.…”
mentioning
confidence: 99%
“…LHD [11,12] is a superconducting magnet system composed of an L 2͞M 10 helical coil and three pairs of poloidal coils. The currents in these coils are fed independently, allowing us to change the shape and position of the magnetic surfaces as well as the magnetic field strength on axis B ax up to 3 T. The plasmas we analyze in this Letter were produced in two magnetic configurations with different magnetic axis positions: R ax 3.75 and 3.6 m. The poloidal cross sectional views of magnetic field lines at a horizontally elongated section are shown for the R ax 3.6 and 3.75 m configurations in Figs.…”
mentioning
confidence: 99%
“…It has a set of L = 2/M = 10 helical coils with a major radius of 3.9 m (Motojima et al 1999). Recent LHD experiments revealed that plasmas can be confined relatively well even under the magnetic configuration with vacuum magnetic axis position R ax = 3.6 m, which is considered unstable in the sense of Magnetohydrodynamic (MHD) instability.…”
Section: Introductionmentioning
confidence: 99%
“…In this situation, a Tracer-Encapsulated Solid Pellet (TESPEL) [1,2] was developed to promote the impurity transport study in the magnetically-confined plasma. The impurity transport study with the TESPEL technology has been performed mainly in the Large Helical Device (LHD) [3,4] at the National Institute for Fusion Science (NIFS) in Japan, and is currently planned in the TJ-II stellarator [5] at the National Fusion Laboratory in the Research Center for Energy, Environment and Technology (CIEMAT) in Spain [6]. The TESPEL is a double-layered impurity pellet.…”
Section: Introductionmentioning
confidence: 99%